Application of Behavior-Based Safety to Reduce Unsafe Actions in Preventive Maintenance Work Using the JSA and DO IT Methods - Aura Irsyaf Putri; Nur, Muhammad; Hartati, Misra; Anwardi; Hadiyul Umam, M. Isnaini (SPECTA Journal of Technology, 2025)
The rapid development of Information and Communication Technology (ICT) in Indonesia has increased the demand for reliable network and telecommunication services. This situation has led to a rise in Preventive Maintenance (PM) activities, which carry high risks of workplace accidents. PT. XYZ is a company operating in the network and telecommunications sector, where PM tasks such as fiber optic cable repairs, cable pulling, joint box lowering, and cable installation repairs are carried out in areas with high potential hazards, including working at heights and near electrical installations. This study aims to reduce unsafe actions during PM activities by implementing the Job Safety Analysis (JSA) method and the DO IT (Define, Observe, Intervene, and Test) approach within the Behavior Based Safety (BBS) framework. The research was conducted using field observations, interviews with workers, and accident data collected from 2023. The results show that unsafe behaviors, such as improper use of personal protective equipment (PPE) and failure to follow standard procedures, still frequently occur. Through the DO IT stages—define, observe, intervene, and test—workers’ awareness of occupational safety increased. The implementation of JSA and DO IT proved effective in identifying potential hazards and designing appropriate interventions to prevent workplace accidents. This study provides recommendations for the company to enhance its occupational health and safety (OHS) management system to create a safer and more productive work environment.